Adverse Events Following Immunization (AEFI) of COVID-19 vaccines and their association with comorbidities in health personnel and public servants in Indonesia - Utami, Wiwik; Rahmawati, Rahmawati; Patonah, Siti; Wahyudi, Imam (Public Health of Indonesia, 2022)
Background: Health workers and public servants as the front line in service are prioritized to get the COVID-19 vaccination. The phenomenon of side effects is a major issue in administering the vaccination. Objective: The research aimed to identify Adverse Events Following Immunization (AEFIs) and their correlation with comorbidities in health workers and public servants in Indonesia. Methods: A cross-sectional study design was used in this study among 262 participants selected using purposive sampling. Data were collected using Google Form. Univariate analysis and Chi-Square were used for data analysis. Results: Of all participants, 74.8% were not comorbid, and 25.2% were comorbid. The incidence of AEFI was 56.9%, relatively occurring after the vaccination I, II, and I and II. AEFI started 40.1% within 24 hours post-vaccination with a 48.7% symptom duration within 1-24 hours. AEFI reactions 42.3% are other reactions in the form of allergic reactions, drowsiness, and increased appetite. The Chi-Square test showed a p-value of 0.894, indicating that both comorbid and non-comorbid patients had the same risk of developing AEFI. Conclusion: Comorbid or non-comorbid is safe to get COVID-19 vaccination. Supervisors reporting on AEFI is important to anticipate the severity condition. Health protocols must be implemented continually.